Girl most likely [videorecording (DVD)] - Simonsen, Rob, 1978- (Lionsgate, 2013)
After both her career and relationship hit the skids, Imogene is forced to make the humiliating move back home to New Jersey with her eccentric mother and younger brother. Adding further insult to injury, there's a strange man sleeping in her old bedroom, and an even stranger man sleeping in her mother's bed.